Crafting Unique Staycation Lodging Packages: Insights from Millennial Lifestyle Segmentation - Astuti, Sherly; Atrisia, Marchela Indah (TIJAB (The International Journal of Applied Business), 2024)
Background: In the post-pandemic landscape, the Tourism and Hospitality Industry, once a cornerstone of the Indonesian economy, experienced a significant downturn. This decline spurred the popularity of "staycations" as an alternative form of tourism among Indonesians. Understanding the perspectives of Indonesian millennial staycation travelers is essential for adapting to evolving travel trends and consumer preferences. Objective: This study aimed to investigate the viewpoints of Indonesian millennial staycation travelers using the Activity, Interests, and Opinion (AIO) model. By employing Lifestyle Segmentation, the overarching goal was to develop tailored Staycation Lodging Packages that cater to the unique interests and behaviors of this target demographic. Method: Exploratory Factor Analysis (EFA) was conducted to identify distinct lifestyle factors, followed by cluster analysis to unveil specific traveler clusters based on their preferences and behaviors. Results: The exploratory factor analysis revealed five distinct lifestyle factors: shopaholic orientation, adventure orientation, foodie orientation, leisure orientation, and cultural and social orientation. Subsequent cluster analysis identified three unique clusters: shopaholic, cultural and social types, leisure types, and foodie types. Each cluster exhibited distinct characteristics and preferences among staycation travelers across various lifestyles. Conclusion: The findings underscore the importance of understanding the diverse preferences and behaviors of Indonesian millennial staycation travelers. By tailoring Staycation Lodging Packages to accommodate these unique interests, businesses in the tourism industry can enhance their marketing strategies and better meet the needs of this burgeoning market segment. Keywords: Lifestyle Segmentation (AIO Model); Lodging Package; Millenial; Staycation; Tourism and Hospitality Industry